Body Image, Eating, and Weight A Guide to Assessment, Treatment, and Prevention (Springer International Publishing, 2018)
This book equips readers with the knowledge required to improve diagnosis and treatment and to implement integrated prevention programs in patients with eating and weight disorders. It does so by providing a comprehensive, up-to-date review of research findings and theoretical assumptions concerning the interface and interactions between body image and such disorders as anorexia nervosa, bulimia nervosa, binge eating disorder, other specified feeding and eating disorders, orthorexia nervosa, overweight, and obesity. After consideration of issues of definition and classification, the opening part of the book examines the concept of body image from a variety of viewpoints. A series of chapters are then devoted to the assessment of the multidimensional construct "body image", to dysmorphophobia/body dysmorphic disorder, and to muscle dysmorphia. The third part discusses body image in people suffering from different eating disorders and/or overweight or obesity, and two final chapters focus on body image in the integrated prevention of eating disorders and obesity, and cultural differences regarding body image. The book will be of interest to all health professionals who work in the fields of psychiatry, clinical psychology, eating disorders, obesity, body image, adolescence, public health, and prevention.